Attraction and Compaction of Migratory Breast Cancer Cells by Bone Matrix Proteins through Tumor-Osteocyte Interactions - Chen, Andy (Sci Rep, 2018)
Bone is a frequent site of metastasis from breast cancer. To understand the potential role of osteocytes in bone metastasis, we investigated tumor-osteocyte interactions using two cell lines derived from the MDA-MB-231 breast cancer cells, primary breast cancer cells, and MLO-A5/MLO-Y4 osteocyte cells. When three-dimensional (3D) tumor spheroids were grown with osteocyte spheroids, tumor spheroids fused with osteocyte spheroids and shrank. This size reduction was also observed when tumor spheroids were exposed to conditioned medium isolated from osteocyte cells. Mass spectrometry-based analysis predicted that several bone matrix proteins (e.g., collagen, biglycan) in conditioned medium could be responsible for tumor shrinkage. The osteocyte-driven shrinkage was mimicked by type I collagen, the most abundant organic component in bone, but not by hydroxyapatite, a major inorganic component in bone. RNA and protein expression analysis revealed that tumor-osteocyte interactions downregulated Snail, a transcription factor involved in epithelial-to-mesenchymal transition (EMT). An agarose bead assay showed that bone matrix proteins act as a tumor attractant. Collectively, the study herein demonstrates that osteocytes attract and compact migratory breast cancer cells through bone matrix proteins, suppress tumor migration, by Snail downregulation, and promote subsequent metastatic colonization.